The Suprachiasmatic Nucleus of the Dromedary Camel (Camelus dromedarius): Cytoarchitecture and Neurochemical Anatomy - El Allali, Khalid; Achaâban, Mohamed R.; Piro, Mohammed; Ouassat, Mohammed; Challet, Etienne; Errami, Mohammed; Lakhdar-Ghazal, Nouria; Calas, André; Pévet, Paul (Frontiers in Neuroanatomy, 2017)
In mammals, biological rhythms are driven by a master circadian clock located in the suprachiasmatic nucleus (SCN) of the hypothalamus. Recently, we have demonstrated that in the camel, the daily cycle of environmental temperature is able to entrain the master clock. This raises several questions about the structure and function of the SCN in this species. The current work is the first neuroanatomical investigation of the camel SCN. We carried out a cartography and cytoarchitectural study of the nucleus and then studied its cell types and chemical neuroanatomy. Relevant neuropeptides involved in the circadian system were investigated, including arginine-vasopressin (AVP), vasoactive intestinal polypeptide (VIP), met-enkephalin (Met-Enk), neuropeptide Y (NPY), as well as oxytocin (OT). The neurotransmitter serotonin (5-HT) and the enzymes tyrosine hydroxylase (TH) and aromatic L-amino acid decarboxylase (AADC) were also studied. The camel SCN is a large and elongated nucleus, extending rostrocaudally for 9.55 ± 0.10 mm. Based on histological and immunofluorescence findings, we subdivided the camel SCN into rostral/preoptic (rSCN), middle/main body (mSCN) and caudal/retrochiasmatic (cSCN) divisions. Among mammals, the rSCN is unusual and appears as an assembly of neurons that protrudes from the main mass of the hypothalamus. The mSCN exhibits the triangular shape described in rodents, while the cSCN is located in the retrochiasmatic area. As expected, VIP-immunoreactive (ir) neurons were observed in the ventral part of mSCN. AVP-ir neurons were located in the rSCN and mSCN. Results also showed the presence of OT-ir and TH-ir neurons which seem to be a peculiarity of the camel SCN. OT-ir neurons were either scattered or gathered in one isolated cluster, while TH-ir neurons constituted two defined populations, dorsal parvicellular and ventral magnocellular neurons, respectively. TH colocalized with VIP in some rSCN neurons. Moreover, a high density of Met-Enk-ir, 5-HT-ir and NPY-ir fibers were observed within the SCN. Both the cytoarchitecture and the distribution of neuropeptides are unusual in the camel SCN as compared to other mammals. The presence of OT and TH in the camel SCN suggests their role in the modulation of circadian rhythms and the adaptation to photic and non-photic cues under desert conditions.